Cooperative Learning Practices in Technology and Livelihood Education among Public High School Teachers - Saturinas, Kristine Paula (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the cooperative learning practices of Technology and Livelihood Education (TLE) teachers in public high schools in City District 1 of Quezon City during School Year 2024–2025. Anchored in Social Constructivism and guided by the Input-Process-Output model, the study aimed to assess teachers’ professional views and current teaching practices related to cooperative learning and to determine whether significant differences existed when respondents were grouped according to selected profile variables. A descriptive research design was employed. Data were gathered from 97 randomly selected TLE teachers out of a population of 128 using an adapted Cooperative Learning Implementation Questionnaire for teachers, which underwent validation and pilot testing and demonstrated acceptable reliability. The data were analyzed using frequency, percentage, weighted mean, Mann-Whitney U Test, Kruskal-Wallis Test, and Dunn Test. The findings showed that most respondents were female, held Teacher I to Teacher III positions, used Taglish as the language of instruction, and were mainly teaching Family and Consumer Science and Information and Communications Technology. Think-pair-share and role-playing emerged as the most commonly used cooperative learning methods. The study further revealed that TLE teachers demonstrated a high level of cooperative learning practice in terms of both their professional views and their current teaching practices. In particular, teachers strongly recognized the value of cooperative learning in increasing student enthusiasm, improving social skills, and supporting academic achievement, motivation, and self-esteem. No significant differences were found in cooperative learning practices when respondents were grouped according to sex, years of teaching, language of instruction, teaching position, TLE specialization, and methods of cooperative learning being practiced. A significant difference was identified only in current teaching practices when respondents were grouped according to the number of years in implementing cooperative learning, indicating that actual and sustained use of cooperative learning strengthened classroom practice. The study concluded that cooperative learning was widely and positively practiced among TLE teachers and recommended professional development initiatives, curriculum support, school-based program implementation, and further studies on cooperative learning methods. The study aligns with SDG 4 (Quality Education), with additional relevance to SDG 8 (Decent Work and Economic Growth) and SDG 17 (Partnerships for the Goals) due to its focus on instructional quality, employability-related skills, and collaborative learning. Its sustainability impact lies in strengthening educational and institutional sustainability through improved pedagogy, teacher development, and the promotion of collaborative competencies relevant to school, work, and community life.
Keywords: Cooperative Learning; Current Teaching Practices; Descriptive Research; Professional Views; Public High Schools; Social Constructivism; Technology and Livelihood Education; TLE teachers